Government Intervention in the Financial Market - Wang, Jiang (Review of Financial Studies, 2026)
Abstract Government intervention in the financial market through its own trading fundamentally changes the market’s structure, function, and outcome. I develop a general equilibrium framework to study the impact of government trading on investor welfare. I show that with incompleteness and information asymmetry, the market equilibrium is in general suboptimal, and government intervention can potentially improve investor welfare even with no additional information. However, the actual welfare impact of government intervention is sensitive to the details of the economy and the policy design. Popular policy targets such as price stability, market liquidity, and informational efficiency can have different welfare implications.